Cardiac alterations induced by Trypanosoma cruzi extracellular vesicles and immune complexes. - Alberto Cornet-Gomez; Francisco O'Valle; José M Garrido; Fernando Rodríguez Serrano; Ana I Nieto; Antonio Osuna (PLoS Neglected Tropical Diseases, 2025)
Background Trypanosoma cruzi is a protozoan parasite responsible for American trypanosomiasis or Chagas disease (CD). This disease is characterized by the presence of cardiac or gastrointestinal symptoms in many patients during the chronic phase, with cardiac symptoms being the most common and severe, affecting approximately 30% of all patients. Although the origin of these pathologies remains unclear, several mechanisms have been proposed, involving factors related to T. cruzi and the host immune response. Extracellular vesicles (EVs) have been studied for their role in parasite-host cell communication, in modulating the host's immune response and more recently as diagnostic tools. Methodology and main findings In this study, we describe the role of EVs released by trypomastigotes and the immune complexes (ICs) they form with anti-T. cruzi IgGs (EVs-IgG) in the development of cardiac symptoms compatible with Chagas cardiomyopathy in mice. Autoantibodies detection, electrocardiographic, histopathological, and immunological analyses in mice's hearts were performed. The studies carried out revealed that, while the inoculation of EVs and ICs (seven intravenous injections of 2 µg of EVs and ICs over 21 days) did not elicit the appearance of autoantibodies, it led to ECG alterations (heart rate and PR interval), changes in heart cavity areas and wall thickness, and reduced expression of crucial proteins for heart function (connexin 43, tubulin, and dynein), as well as VCAM-1 and altered the cytokine expression profile in the heart. Finally, both EVs-inoculated and ICs-inoculated mice showed an increased presence of B-type natriuretic peptide (BNP) in serum, suggesting that EVs or ICs may participate in the onset of cardiac damage. Conclusions Our results confirm the ability of EVs shed by the infective forms of T. cruzi and the immune complexes they form with IgG to induce cardiac alterations in mice similar to those described in the literature, in T. cruzi-infected mice as well as in Chagas disease patients. This study highlights the role of EVs in the pathogenicity of Chagas disease and reinforces the importance of considering them as virulence factors in the development of Chagas disease.